Expression of the 14 kDa galactose-binding protein, galectin-1, on human tubular epithelial cells - Bürger, Antje; Filsinger, Sabine; Cooper, Douglas N. W.; Hänsch, Gertrud Maria (Kidney international, 1996)
Expression of the 14kDa galactose-binding protein, galectin-1, on human tubular epithelial cells. By reverse phase PCR and Northern blotting, RNA of the 14kDa galactose-binding protein (galectin-1) could be identified in primary cultures of human tubular epithelial cells. To assess protein synthesis and the possible function of galectin-1 on TEC, the cellular proteins were biosyntheticically labeled with [35S]-methionine and adsorbed to immobilized laminin. Multiple radiolabeled proteins were eluted, a strong band in the area of 14kDa was seen, coinciding with the galectin-1 band as identified by Western blotting. Surface expression of galectin-1 was seen by cytofluorometry with two different polyclonal antibodies to galectin-1. These data are in line with the finding that tubular epithelial cells adhere to laminin, partly in a Ca2+-independent manner.